Organic Architecture as an Approach to Resort Hotels Design in the Simalem Park Tourism Area - B OY Marpaung; Sakinah Hasibuan (Talenta Publisher, 2018)
Indonesian tourism is an industrial sector that is being elevated with the aim of increasing the country's foreign exchange income, and society in general, increase opportunities and employment, encouraging other industrial activities, introducing, empowering the use of natural beauty and Indonesian culture. Karo Regency is a tourist area that many visits, Karo District has nature potentials as a tourist attraction. In general, tourism has the potential for natural and historical tourism. Nature tourism includes lakes, parks, wildlife reserves or nature reserves, and cultural captures. Taman Simalem is one of the tourist areas in Karo Regency. Simalem Park tourist area is currently a tourist area that is a mainstay in Karo district with a large number of visitors who always increase each year. See so many tourism objects in Karo regency; it is necessary to build an accommodation service for tourists who want to vacation and enjoy the tourism objects. In buildings resort hotel accommodation services using organic themes then linking aspects of space that can adapt to the natural environment. The organic architectural theme approach is expected to facilitate the application of concepts that take shape from nature.